2020
DOI: 10.1002/wsbm.1504
|View full text |Cite
|
Sign up to set email alerts
|

The shifting shape and functional specializations of the cell cycle during lineage development

Abstract: Essentially all cell cycling in multicellular organisms in vivo takes place in the context of lineage differentiation. This notwithstanding, the regulation of the cell cycle is often assumed to be generic, independent of tissue or developmental stage. Here we review developmental‐stage‐specific cell cycle adaptations that may influence developmental decisions, in mammalian erythropoiesis and in other lineages. The length of the cell cycle influences the balance between self‐renewal and differentiation in multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 97 publications
0
18
0
Order By: Relevance
“…Taken together, both transcriptional and functional approaches suggest remarkable remodeling of the cell cycle that takes place in lock step with developmental events of the erythroid trajectory [16,19,20,23,32]. We observe cells undergoing gradual shortening in G1 as they progress through the BFU-e and CFU-e stages; this is followed by an abrupt shortening in S phase at the CFU-e/ETD switch.…”
Section: The Transcriptional Context Of the Cfu-e/etd Switch Is Domin...mentioning
confidence: 72%
See 1 more Smart Citation
“…Taken together, both transcriptional and functional approaches suggest remarkable remodeling of the cell cycle that takes place in lock step with developmental events of the erythroid trajectory [16,19,20,23,32]. We observe cells undergoing gradual shortening in G1 as they progress through the BFU-e and CFU-e stages; this is followed by an abrupt shortening in S phase at the CFU-e/ETD switch.…”
Section: The Transcriptional Context Of the Cfu-e/etd Switch Is Domin...mentioning
confidence: 72%
“…What is the relevance of these findings to non-erythroid lineages? Although some aspects of cell cycle regulation had been known to be relevant to development for some time, the relevance of S phase duration is becoming clearer only recently [32]. S phase shortening at the onset of mammalian gastrulation had been known for many decades [36,[43][44][45], but was perhaps considered unique to this critical developmental milestone.…”
Section: Summary and Wider Context: The Role Of The Cell Cycle In Cel...mentioning
confidence: 99%
“…Unexpectedly, DNA damage checkpoint kinases (ATM, ATR, and CHEK2) were also enriched. During terminal maturation, erythroblasts undergo a series of specialized cell divisions associated with shortened G1 phase and increased lineage-specific gene expression (Hwang, Hidalgo et al, 2020). It is possible that DNA damage checkpoint activity is triggered to control replicative stressinduced damage during this process, similar to what occurs upon ▸ A Heat map of z-scored and differentially regulated kinase and phosphatase abundances (log2 DIA intensities) across differentiation.…”
Section: Computational Extraction and Characterization Of Stage-specific Protein Markersmentioning
confidence: 99%
“…Different phases of cell cycle (G1, S, G2 and M) are closely related to key regulatory molecules of cell cycle. Since the length of cell cycle is mainly determined by the length of G1 phase, the most important regulatory targets exist in G1 phase [34,35]. Our study showed that ESCC cells with SK treatment could be stagnated in the G0/G1 phase instead of entering the S phase for DNA replication via inhibiting the expression of 10 Cyclin D1 and CDK4.…”
Section: Discussionmentioning
confidence: 68%